The History of Anemia in Pregnancy with Stunting Incidents in Toddlers at Nipah Community Health Center, Malaka, North Lombok Regency - Rifana Cholidah; Ario Danianto; Rahmah Dara Ayunda; Devi Rahmadhona (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting is a chronic nutritional problem whose incidence is quite high in Indonesia. Efforts to prevent and reduce stunting rates must involve all parties comprehensively. The process of stunting starts from pre-conception when a teenager becomes a mother who is malnourished and anemic. In Indonesia, 37.1% of women of childbearing age suffer from anemia. Several studies report that there is a relationship between anemia in pregnancy and the incidence of stunting in toddlers, however similar research is still rarely carried out in West Nusa Tenggara (NTB). This study aims to determine the relationship between a history of anemia in pregnant women and the incidence of stunting in toddlers at the Nipah Community Health Center, Malaka, North Lombok Regency (KLU). This research is an observational analytical survey research with a case control design. There were 69 samples in the case group (stunted toddlers) and 69 samples in the control group (normal toddlers). The results showed that there were 101 mothers (73.2%) with normal Hb levels, 24 mothers (17.4%) with mild anemia and 13 mothers (9.4%) with moderate anemia. Overall, 37 mothers (26.8%) suffered from anemia. The conclusion of this study is that there is no significant relationship between a history of anemia in pregnancy and the incidence of stunting in toddlers with a p value of 0.842. Obtaining an odds ratio value of 1 means that mothers who experience anemia during pregnancy have no risk of having stunted children. Anemia during pregnancy, parental income, education level and mother's employment simultaneously influence the stunting variable by 14.9%.